Procyclical Behavior of Institutional Investors During the Recent Financial Crisis : Causes, Impacts, and Challenges - Papaioannou, Michael (IMF Working Papers; Working Paper ;, 2013)
This paper (i) provides evidence on the procyclical investment behavior of major institutional investors during the global financial crisis; (ii) identifies the main factors that could account for such behavior; (iii) discusses the implications of procyclical behavior; and (iv) proposes a framework for sound investment practices for long-term investors. Such procyclical investment behavior is understandable and may be considered rational from an individual institution's perspective. However, our main conclusion is that behaving in a manner consistent with longterm investing would lead to better long-term, risk-adjusted returns and, importantly, could lessen the potential adverse effects of the procyclical investment behavior of institutional investors on global financial stability.